Indigenous values and perspectives for strengthening food security and sovereignty: learning from a community-based case study of Misko-ziibiing (Bloodvein River First Nation), Manitoba, Canada - Young, Lisa; Shukla, Shailesh; Wilson, Taylor (Frontiers in Sustainable Food Systems, 2024)
Despite food security being a significant challenge among many First Nations communities on Turtle Island, there needs to be more empirical, community-based research that underscores the role of traditional food systems and associated values and teachings in Manitoban communities through an Indigenous lens. This research addresses that gap by building upon Indigenous perspectives and knowledges on the status and future directions of food security and sovereignty in Misko-ziibiing (Bloodvein River First Nation). Guided by Indigenous research protocol and using a qualitative research approach, ten in-depth interviews with Bloodvein River First Nation (BVR) and Winnipeg Elders were conducted. Data was also sourced through discussions with local council members, participant observation, and field visits during 2017. The fundamental values and traditional teachings associated with food sovereignty within the community are aligned with the spirit of sharing, including sharing ethics and protocols, social learning within the community, and intergenerational transmission. In recent years, changing environmental, developmental activity, government policies and laws, lifestyle changes and affordability dynamics have continued to threaten the self-determination and food sovereignty of Indigenous peoples in the community. Their perspectives, teachings, and voices are rarely present in any scholarly work. Enhanced intergenerational transmission of traditional teachings, education and language revitalization, and local leadership involvement can strengthen these social and cultural values to enhance Indigenous food security and sovereignty in Miskoziibiing. This research identifies the knowledge and views of Elders, hunters, trappers and fishers, contributing to the current studies associated with traditional food systems and teachings. Strengthening social and cultural traditions and values is vital in working towards Indigenous food governance, sovereignty, and revitalization of their Indigenous food systems.